MEMPERBAIKI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MENGGUNAKAN PEMBELAJARAN REMIDIAL - Floviana Yosefa Dessy (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2017)
This research aims to describe student’s error in finishing Mathematics’ question dealing with probability material and the causes of student’s error and it purposes to know whether remedial program can fix those errors or not. The result of the diagnosis test shows that the students encounter concept error, principal error, technique error, and factual error. The causes of these errors: (1) the students do not know the correct way to solve the question, (2) the students cheat their classmate, (3) the students are lazy to study mathematics, (4) the students do not study mathematics at home, (5) the students do not understand probability concept well, (6) they are not interested in mathematics because they think it is difficult, (7) the students do not like mathematics since they were in elementary and junior high school, (8) the students are not interested in mathematics because they think mathematics which is learned at school is not used in daily life, (9) the students do not like mathematics so they are unwilling to join the lesson at school, (10) the students are lazy to study and pay attention in the class so they do not understand the material, (11) the student cannot focus on the material which is given in the class, (12) The class’s situation does not support them to study, (13) the students do the diagnosis test in hurry (14) they are not conscientious in finishing diagnosis test. Based on the research, remedial program has not fixed the students’ error yet.